If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8(r + -5)(r + 5) = 0 Reorder the terms: 8(-5 + r)(r + 5) = 0 Reorder the terms: 8(-5 + r)(5 + r) = 0 Multiply (-5 + r) * (5 + r) 8(-5(5 + r) + r(5 + r)) = 0 8((5 * -5 + r * -5) + r(5 + r)) = 0 8((-25 + -5r) + r(5 + r)) = 0 8(-25 + -5r + (5 * r + r * r)) = 0 8(-25 + -5r + (5r + r2)) = 0 Combine like terms: -5r + 5r = 0 8(-25 + 0 + r2) = 0 8(-25 + r2) = 0 (-25 * 8 + r2 * 8) = 0 (-200 + 8r2) = 0 Solving -200 + 8r2 = 0 Solving for variable 'r'. Move all terms containing r to the left, all other terms to the right. Add '200' to each side of the equation. -200 + 200 + 8r2 = 0 + 200 Combine like terms: -200 + 200 = 0 0 + 8r2 = 0 + 200 8r2 = 0 + 200 Combine like terms: 0 + 200 = 200 8r2 = 200 Divide each side by '8'. r2 = 25 Simplifying r2 = 25 Take the square root of each side: r = {-5, 5}
| -4x+2+7x+3= | | 9x+4x-8x=8+7 | | 2(x-3)=(2x+5) | | 6y+2(3+6.5y)=2.5+15.5y | | 3+1b=5 | | 11p-9+8p-7+14=12p+9p+4 | | 8x-24y=144 | | 0.5r+5.2=2.8 | | 7(24-x)=5x | | 4x^2-2ax-2bx+ab=0 | | 12-k=22 | | 4x-16y=144 | | 0.4y+8=-2 | | 5[-3(4x+5)+3(5x-4)]= | | -14+11p-10p-6= | | -18+12f+16f+15= | | -5x-3y=16 | | (6)*(-7)= | | 18c+4c+7-9= | | -14-(-1.5)= | | -6+2x-3-10x= | | -22-22= | | b^4+12b^2p^2+36p^4= | | 21+(-19)+(-24)= | | -7x^2-13x+2=0 | | x+20x=1 | | 6=9k-12 | | 6.4+(-0.9)= | | 11n^2-16=0 | | 2y^2-4xy+3=0 | | 7r+5+19+3r= | | -3.4+9.6= |